Teaching Innovations in Public Health Education: Integrating Simulation and Case-Based Learning - Maria Helena; Theresa Cecilia; Agnes Kristina (Generasi Sains Indonesia, 2025)
This study examines the integration of simulation-based learning and case-based learning in public health education to explore their influence on student engagement, critical thinking, collaborative problem-solving, and reflective learning. Using a qualitative phenomenological approach, data were collected through semi-structured interviews, focus group discussions, reflective journals, and classroom observations involving undergraduate public health students and educators. The findings indicate that simulation activities enhanced active participation, communication, confidence, and experiential engagement, while case-based learning strengthened analytical reasoning, contextual understanding, and evidence-based decision-making. The integration of both approaches created a collaborative learning environment that connected theoretical knowledge with practical public health application. The novelty of this study lies in its integrated examination of simulation and case-based pedagogies within public health education from both student and educator perspectives. The findings imply that experiential and student-centered learning approaches can support curriculum innovation and improve professional preparedness for addressing complex public health challenges in higher education settings.